2016
DOI: 10.1002/cbic.201600261
|View full text |Cite
|
Sign up to set email alerts
|

Interrogating the Tailoring Steps of Pactamycin Biosynthesis and Accessing New Pactamycin Analogues

Abstract: Pactamycin is a bacteria-derived aminocyclitol antibiotic with a wide-range of biological activity. Its chemical structure and potent biological activities have made it an interesting lead compound for drug discovery and development. Despite its unusual chemical structure, many aspects of its formation in nature remain elusive. Using a combination of genetic inactivation and metabolic analysis, we investigated the tailoring processes of pactamycin biosynthesis in Streptomyces pactum. The results provide insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 16 publications
1
34
0
Order By: Relevance
“…The late stage of the biosynthetic pathway of pactamycin has been characterized by Mahmud and co‐workers (Scheme bottom reaction steps) . They constructed various mutant strains of S. pactum , which accumulated intermediates of pactamycin biosynthesis, to propose the biosynthetic pathway.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The late stage of the biosynthetic pathway of pactamycin has been characterized by Mahmud and co‐workers (Scheme bottom reaction steps) . They constructed various mutant strains of S. pactum , which accumulated intermediates of pactamycin biosynthesis, to propose the biosynthetic pathway.…”
Section: Methodsmentioning
confidence: 99%
“…They constructed various mutant strains of S. pactum , which accumulated intermediates of pactamycin biosynthesis, to propose the biosynthetic pathway. A double‐knockout mutant of ptmH ( pctJ ), which encodes a cobalamin‐dependent radical S ‐adenosyl‐ l ‐methionine (SAM) methyltransferase, and ptmD ( pctF ), which encodes a SAMdependent N ‐methyltransferase, was shown to accumulate TM‐101, a supposed intermediate of pactamycin biosynthesis . Cytochrome P450 oxygenase PtmY (PctA) seems to be involved in the hydroxylation reaction of late‐stage biosynthesis, although disruptive mutations of ptmY ( pctA ) do not completely abolish pactamycin production .…”
Section: Methodsmentioning
confidence: 99%
“…However, 3AAP was not incorporated into pactamycin; this indicated that the physiological substrate of PctL was 3ABA or its thioester derivatives such as 3‐aminophenyl‐β‐oxopropanoic acid thioester, which would undergo hydrolysis and decarboxylation to give the 3AAP moiety . Mahmud and co‐workers reported that a mutant with a knockout of a discrete acyl carrier protein PtmL (PctK) did not accumulate any pactamycin biosynthetic intermediates . Because no biosynthetic intermediate between 3ABA and TM‐101 has so far been isolated, the intermediates in the early stage of biosynthesis seem to be hydrophilic thioesters with acyl carrier protein (ACP; Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…However, in 2011, TM‐025 1 b , obtained by bioengineering, exhibited an improved profile displaying a greater cytotoxicity against Plasmodium falciparum as compared to mammalian cells. Similarly, Jogyamycin 1 c , another natural product analogue, showed potent antimalarial and antitrypanosomal activities, with IC 50 values of 1.5 and 12.3 nM, respectively [4–5] . These analogues, including de‐6MSA‐pactamycin 1 d , are structurally less complex and more stable than pactamycin 1 a .…”
Section: Occurrencementioning
confidence: 99%